The Effect of a Ketogenic Diet on Human Health and Diseases: A Literature Review - Bielas, Kinga; Chodkowska , Ewa; Dominiczak, Kinga; Szafrańska, Katarzyna; Mucha, Aleksandra; Szeps, Aleksander; Zabrzeński, Bartosz; Schendzielorz, Jessika (Quality in Sport, 2025)
Introduction and Aim. The ketogenic diet (KD), rich in fats and low in carbohydrates, induces a state of ketosis and metabolic changes. Used for over a century in epilepsy treatment, it is also gaining popularity in the therapy of other conditions, including metabolic, cardiovascular, oncological, and neurodegenerative diseases. The aim of this work is to review the literature concerning its effects, applications, and potential adverse effects. Methods. A review of PubMed and Google Scholar databases from the last five years was conducted, focusing on clinical studies, meta-analyses, and systematic reviews, using keywords: "ketogenic diet", "ketogenic diet and health”, "ketogenic diet mechanisms" and “ketogenic diet adverse effects”. State of Knowledge. The KD promotes weight loss and improves glycemic control in patients with type 2 diabetes, and in type 1 diabetes, it may reduce insulin requirements; however, caution is necessary due to risks of hypoglycemia and ketoacidosis. The effects on lipid profiles are inconclusive. The diet can support cancer treatment by limiting glucose and insulin availability and exhibits neuroprotective effects in neurodegenerative diseases such as drug-resistant epilepsy, Alzheimer’s disease, and Parkinson’s disease. However, it may also be associated with side effects such as constipation, hypoglycemia, kidney stones, and lipid disturbances. Summary. The KD has therapeutic potential but requires monitoring, especially with long-term use, due to possible adverse effects. Further research is needed to assess its long-term efficacy and safety, particularly in the treatment of neurodegenerative and oncological diseases, to fully evaluate its therapeutic potential.